SCENT AS A MEANS OF VISUALIZING AN ARTISTIC CONCEPT IN THE DESIGN OF PRINTED PRODUCTS - Skliarenko, Nataliia; Romaniuk, Olha; Kolosnichenko, Maryna (Theory and practice of design, 2024)
Purpose. The aim of the study is to define the concept of visualizing an artistic image using scents in design of printed products. Methodology. The methodology of the study is based on the using of system and synergistic approaches, which make it possible to explain the ways of the integration of scents into visual communications, their transdisciplinary interconnections with people and environment. The artistic images of scented printed products visualization were analyzed using compositional, and system and functional design analyses. Results. In the study, the role of scent in visualization of artistic and figurative concept of printed products has been pointed out. It has been proved that scent is the key element of the product and provides effective communication with a consumer, activates memory and forms corresponding emotions. Emotional, narrative, educational and environmental concepts of visualization of scented artistic image were pointed out in design of scented printed products. It has been defined that innovative technology (e.g. interactive scent, encapsulation, infusion, scented ink, diffusion), which activate several sensory systems simultaneously and form the phenomenon of synesthesia, are spreading in printed products design. Scientific novelty. In the work, the role of scent was comprehensively considered in the development of concepts of printed products design from the standpoint of the system approach for the first time. It has been proved that design of olfactory visual communications, for example scented printed products, and is an effective way of person’s behavior programming. Practical relevance. The materials of the study are the base for the creation of versatile concept of artistic image visualization in printed production design. The results of the work can be used by the specialists of various fields to form innovative strategies for integrated visual communications in the conditions of constantly changing information environment.